Relevance of Inflation Control According to M. A. Mannan With Law No. 3 Of 2004 - Mabruri Andatu; Tajul Arifin (UIN Siber Syekh Nurjati Cirebon, 2024)
This research is motivated by the frequent inflation challenges faced by Indonesia, attributed to the limited integration of sharia principles in maintaining economic stability. The study aims to analyze the compatibility of M. A. Mannan's inflation control mechanisms with the provisions of Law No. 3 of 2004 on Bank Indonesia, particularly Article 10 Paragraph 1. Mannan's concept offers a mechanistic approach to understanding the factors affecting inflation and effective control methods. This study examines the alignment between Mannan's principles and existing legal frameworks, including the role of Bank Indonesia in ensuring price stability. The findings reveal that, despite theoretical and practical differences, Mannan's proposed mechanism complements the strategies outlined in the law, providing valuable insights for effective monetary policymaking. This research adopts a normative juridical approach and descriptive analysis method, with data collected and analyzed using qualitative techniques. The results indicate notable differences and similarities between Indonesia's inflation control and Mannan's monetary policy concept. The findings underscore the importance of integrating Mannan's approach into Indonesian monetary policies to enhance inflation control and national economic stability.Keywords: Inflation Policy, Islamic Economy, M.A.Mannan, Bank Indonesia, Price Stability